Об аналитическом методе факторизации составных чисел - Семотюк, М.В. (Комп’ютерні засоби, мережі та системи, 2013)
Трудности факторизации чисел сводятся к тому, что в кольце целых чисел существует одно уравнение, представляющее их произведение. Применение колец вычетов по модулю позволяет получить второе уравнение. Труднощі факторизації чисел зводяться до того, що в кільці цілих чисел існує одне рівняння, що представляє їх добуток. Використання кілець залишків по модулю дозволяє отримати друге рівняння. Difficulties factoring composite numbers reduced to the fact, that in the ring of integers there is only one equation that represents is a product of the numbers. The use of residue rings modulo allows you to get the second equation. This significantly reduces the computational cost.